Development and clinical significance of the musculus dorsoepitrochlearis in men - Haninec, P; Tomás, R; Kaiser, R; Cihák, R (Clinical anatomy (New York, N.Y.), 2009)
Musculus dorsoepitrochlearis is a typical muscle variation, which, if in full extent, is represented by the muscular or fibromuscular slip detached from the anteroinferior border of the musculus latissimus dorsi. It passes over the axilla under the axillary fascia crossing the medial side of the brachial plexus and continues as a septum intermusculare mediale brachii distally to the medial epicondyle of humerus. Its full extent is rarely developed-the connection into the intermuscular septum being mostly absent. Muscular slips from the musculus latissimus then insert on various structures in the axilla, often on the crest of greater tubercle of humerus or into the musculus pectoralis major (this variation is known as the axillary arch of Langer) or to other neighboring structures (coracoid process, fasciae of muscles). In our observations, 209 patients with traumatic lesions of the brachial plexus underwent surgical procedure. The presence of the musculus dorsoepitrochlearis has been observed. It was found in the form of various slips from the musculus latissimus dorsi in 4 patients. In 3 of those 4 patients, the innervation was derived from the nervus thoracodorsalis. We also presented 2 case reports of patients with clinical symptoms caused by compression of nerves in the axilla by the dorsoepitrochlear strip.
Keywords: Young Adult; humerus; Axilla; Male; Child, Preschool; mladý dospělý; nervus ulnaris; Adolescent; Infant; Child; dítě; Adult; Muscle, Skeletal; Aged; dospělí; mužské pohlaví; senioři; prsní svaly; Ulnar Nerve; mladiství; kosterní svaly; předškolní dítě; úžinové syndromy; Humerus; lidé; ženské pohlaví; Humans; hrudní nervy; Nerve Compression Syndromes; axila; kojenec; Thoracic Nerves; Thoracic Wall; Pectoralis Muscles; hrudní stěna; Female; lidé středního věku; Middle Aged